Fatigue and stress reactivity are differently related to cigarette craving and hormone responses to neurotransmitter related drugs in nicotine deprived smokers. (1st November 2017) - Netter, Petra; Hennig, Juergen
Abstract: Lack of drive in depression has been reported to derive from deficiency of dopamine, whereas high responsiveness of the noradrenergic and serotonergic system have been found to be associated with anxiety related components of depression. Since, furthermore, the three neurotransmitters and depression are relevant in smoking motivation, the present experiment investigates if fatigability (FA) and stress reactivity (SR), the two corresponding components of depressiveness measured as personality dimensions in the normal range, can be separated by drug induced hormone responses and cigarette craving and their combined effects. Method: 36 Healthy male smokers assessed for FA and SR by questionnaires were tested under noradrenergic (NA), serotonergic (5-HT) and dopaminergic (DA) pharmacological stimulation in a placebo controlled balanced crossover design with respect to time and size of drug induced hormone responses and measures of cigarette craving during nicotine deprivation. Results: Revealed that both FA and SR were related to early 5-HT responses but only FA showed late and low DA responses confirming the DA deficiency hypothesis. Smoking urge was increased by the noradrenergic drug merely in stress sensitive individuals, and larger prolactin responses to DA were associated with increased smoking urge. Conclusions: Facets of depressiveness can be discriminated by neurotransmitter related hormone responses. Personality related differences in motivation may be revealed by psychotropic drugs, and their underlying mechanisms may become evident by neurochemical responses to psychotropic drugs. Highlights: The facets of depression, and stress sensitivity, can be discriminated by transmitter related drug responses Noradrenergic drugs may increase smoking urge in stress sensitive smokers Fatigability is associated with lack of dopamine production indicated by low and late hormone response Smoking urge is related to high dopamine release confirming incentive stimulation theory of dopamine